Effects of probiotics on heart failure: a systematic review and meta-analysis - Zhu, Zheqin; Chen, Aoli; Wang, Min; Zhang, Huimin; Dai, Sisi; Liu, Rongzhen; Liu, Jianhe (Frontiers in Nutrition, 2025)
BackgroundHeart failure (HF) is a serious clinical syndrome with substantial health threats. Emerging studies link intestinal flora dysbiosis to HF onset and progression. Although probiotics are thought to regulate gut microbiota, the specific impact of probiotics on HF remains unclear, highlighting the need for systematic evaluation.MethodsAs of 9 September 2025, we searched eight major academic databases using a predefined protocol for data extraction and quality assessment. Subsequently, a meta-analysis was conducted using Review Manager 5.4 and Stata 18. Forest plots were used to analyse the effect size, and publication bias was evaluated through funnel plots.ResultsUltimately, 11 of the studies met the inclusion criteria for the systematic review. The results showed that probiotics have a slight beneficial effect on cardiac function indicators (LVEF, LVESV), reduced the levels of inflammatory factors (hs-CRP, IL-6, TNF-α), regulated the proportion of dominant gut bacteria, and decreased the readmission rates of patients with HF. However, no beneficial effects were found on NT-proBNP, activity endurance, TMAO, and mortality.ConclusionProbiotics exert cardioprotective effects and can serve as adjunctive therapy for HF management. Future high-quality, large-sample clinical studies are needed to further clarify their long-term efficacy and optimal intervention strategies.Systematic review registrationDetails of the protocol for this systematic review were registered on PROSPERO (CRD420251083960).